Audit Independence Threats and Safeguards in Non Audit Service Provision (gjstudies, 2025)
This research investigates the complex dynamics of audit independence within thecontext of non-audit service (NAS) provision, proposing a novel, multi-dimensionalframework for assessing threats and evaluating safeguards. While existing literature predominantly focuses on financial metrics and regulatory compliance, thisstudy introduces a behavioral and cognitive perspective, examining how auditorclient relationships evolve during NAS engagements and how these relationshipssubtly influence judgment and objectivity. We employ a mixed-methods approachcombining experimental simulations with longitudinal case studies of audit firmsthat have integrated NAS into their service portfolios. Our methodology uniquelyincorporates elements from behavioral economics, social network analysis, and professional identity theory to map the latent pathways through which independencemay be compromised, moving beyond the overt financial dependencies typicallyscrutinized. The findings reveal that the most significant threats often emergefrom relational capital and cognitive alignment developed during NAS work, whichcan unconsciously bias audit planning and materiality judgments. We identify apreviously under-researched ’consultancy mindset carryover’ effect, where problemsolving approaches honed in advisory roles permeate audit execution. In response,the paper proposes and tests a set of innovative safeguards, including ’cognitivefirewalling’ protocols, mandatory perspective-taking exercises for audit teams, andthe use of algorithmic monitoring tools to detect shifts in professional judgmentpatterns. The results demonstrate that structural and procedural safeguards aloneare insufficient; reinforcing the auditor’s professional identity as a protector of public interest is equally critical. This research contributes a more nuanced, humancentric model for protecting audit independence, offering practical tools for firms,regulators, and educators to strengthen the foundational integrity of the financialreporting ecosystem in an era of expanding professional service scope.